TANGGUNG JAWAB MALL YANG MENGADAKAN RENOVASI BANGUNAN TERHADAP PENYEWA (TENANT) BERDASARKAN PERJANJIAN SEWA-MENYEWA - Nadira Saraswati, Luh Ayu; Satyayudha Dananjaya, Nyoman (Kertha Semaya : Journal Ilmu Hukum, 2015)
This paper title Responsibility of Mall Manager Who Conduct Renovations To Tenant Based on The TenancyAgreement is motivated by the rapid development of the business world that involvingThe Mall Manger and The Tenant. To run the businessboth parties signing tenancy agreement . Due to improving the service to visitors, the manager of the mall will do a renovation, which can give an impact to the Tenant. This study aims to find out the regulation of tenancy agreement and the responsibility of the mall manager to the tenantthat affected by the renovation of the building based on the tenancy agreement. With normative method, this paper elaborate more about the regulations of tenancy agreementthat stated on article 1548-1600 Civil Code and the responsibility of the mall manager who conduct renovations to providing peaceful enjoyment during the lease for the tenant.
Keywords: Responsibility,The Mall Manager, Renovation, Lease and Rent Agreement